The Integration of Engineering Accounting and Cost Accounting to Improve the Accuracy of Environmental Cleanup Costs in Iraqi Oil Companies - Mohammed, Iman Shakir (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study aims to explore the integration of engineering accounting and cost accounting to enhance the accuracy of environmental cleanup costs in Iraqi oil companies. Through quantitative and qualitative data analysis, the research examines the effectiveness of this integration, using a case study that combines semi-structured interviews with senior accountants and environmental engineers, along with internal reports' data analysis and environmental and economic impact assessments.The findings reveal a mixed relationship between engineering data integration and perceived benefits, with positive perceptions prevailing despite limited demographic variables' statistical impact.The study highlights significant future implications for oil companies, which face challenges in determining actual environmental cleanup costs due to reliance on traditional accounting methods. The integration of engineering and cost accounting is expected to improve environmental cost accuracy, boost operational efficiency, enhance transparency and accountability in environmental reporting, and mitigate potential risks in Iraqi oil companies